Teaching Faith in Angels for Junior High School Students - Amin, Alfauzan; Alimni, Alimni; Kurniawan, Dwi Agus (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
The purpose of this study was to analyze students in understanding ”faith in angels”. Also, the researchers tried to provide handouts with the example and non-example learning model and conventional model. This study employed the mixed-method approach, where the researchers used quantitative and qualitative data in formulating the results. The sample consisted of 68 junior high school students. The sample was determined by a total sampling of students studying Islamic Education at the Bengkulu school. The results showed that the concept of students' understanding of faith in angels was categorized as good. Furthermore, there is no significant difference between the use of the example and non-example model or the conversion model with handouts. The handouts made can make it easier to understand the concept of faith in angels even though they are used using the example and non-example and conventional model. The research with the handout of ”faith in angels” makes it easier for students to learn Islamic Education because it includes the picture and example real-life existence of angels.